Managing IT business-alignment through the implementation of IT balanced scorecard: a proposed framework / Hardy Santosa Sundoro, Harimukti Wandebori - Sundoro, Hardy Santosa; Wandebori, Harimukti (Faculty of Information Management, 2021)
We propose an integrated methodological framework system to synthesise and implement the IT Balanced Scorecard (BSC). The proposed approach capitalises on existing information and incorporates essential questions that were not routinely considered or recorded in previous work. The approach aims to address several serious challenges which many implementations face by recognising weaknesses and critical success factors from the literature review. The aim of this proposed framework specifically to provide a guideline for business-IT to achieve a better alignment.